Non-profit organizations marketing activities in the role of motivating young people to volunteer - Glavinić, Jerko; Najev Čačija, Ljiljana (Oeconomica Jadertina, 2018)
The non-profit sector of recent decades arises the interest of researchers and the public not only for its growth, but also the benefits it brings to the entire society. Non-profit organizations are sectoral development initiators, whereby human resources are also needed to achieve targets oriented at different target groups. In order to successfully dedicate non-profit organizations to target groups, the paramount importance is assigned to performance of marketing activities. Key segments, namely target groups, are represented by users, donors, volunteers, employees and the general public. In the context of human resources, volunteers play a major role. Therefore, one of the tasks of marketing activities is the motivation of volunteers for their engagement. The aim of this paper is to examine the impact of non-profit organizations marketing activities on six motivational functions of volunteering among young people. These functions are: protection, values, career, society, understanding and respect. Research results suggest that marketing activities have a positive impact on motivational functions of protection and career, whereas this impact has not been confirmed on the function of understanding and value. The impact was partially confirmed on the function of society and respect. The results of the research contribute to a better understanding of volunteer motivation and the active role of the organizations in its development by applying the optimal combination of marketing activities.